2022
DOI: 10.1038/s41598-022-10272-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the pulse electric field assisted extraction of black rice grain for antioxidant and sirtuin1 enzyme stimulation activities

Abstract: Cyanidin-3-glucoside (C3G) and peonidin-3-glucoside (P3G) in black rice grain (BRG) demonstrate many beneficial health effects, including antioxidant and anti-aging properties. This research aimed to study on pulsed electric field assisted water extraction (PEF-AWE) on BRG using pre-treatment technique, which was determined for enhanced yields of C3G and P3G, antioxidant and sirtuin1 enzyme stimulation activities. The effects of operating parameters for PEF-AWE (intensity of electric field, X1: 3–5 kV/cm, numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The PEF machine used in this study was similar to that used in research of Salee et al . (2022). The extraction chamber had a rectangular shape of 4 × 13 cm, with electrodes spaced 2 cm apart.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PEF machine used in this study was similar to that used in research of Salee et al . (2022). The extraction chamber had a rectangular shape of 4 × 13 cm, with electrodes spaced 2 cm apart.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison, hot water extraction was performed by mixing the powder with distilled water at a ratio of 1:30 and subsequent heating at 100 °C for 6 h (Smiderle et al, 2013). The PEF machine used in this study was similar to that used in research of Salee et al (2022). The extraction chamber had a rectangular shape of 4 × 13 cm, with electrodes spaced 2 cm apart.…”
Section: Extraction and Purification Of Polysaccharidesmentioning
confidence: 99%
“…The surtuin1 Activity Assa Kit (Fluorometric) of Abcam (ab156065) was used to evaluate the surtuin1 enzyme-stimulating activity of extract in accordance with the instructions from manufacturer. The in vitro assay of surtuin1 enzyme-stimulating activity of extract was examined according to Salee et al (2022). The mixture solution of water HPLC-grade (25 µL), surtuin1 assay buffer (5 µL), fluoro-substrate peptide (5 µL) and NAD (+)-dependent histone deacetylase (5 µL) was added and mixed gently to the wells of a microtiter plate.…”
Section: Determination Of the Surtuın1 Enzyme-stimulating Activitymentioning
confidence: 99%
“…Black rice (Oryza sativa L.) is a type of pigmented rice that contains significant amounts of anthocyanins in the bran layer, and is regarded as an effective health-promoting functional food. Anthocyanin from black rice was identified by cyanidin-3-glucoside (C3G) and peonidin-3-glucoside (P3G) (Salee et al, 2022) which demonstrated scientifically proven health benefits, as well as promoted immune responses in leukemia (Fan et al, 2017), anti-diabetes and hyperlipidemia (Yang et al, 2011;Zhang et al, 2013) and cholesterol and lipid metabolism. Colored rice could affect the expansion of life-span by reducing the reactive oxygen species (ROS) via Sir2-dependent signaling pathways, with human homologs of NAD-dependent deacetylase sirtuin-1 (surtuin1) (Sunthonkun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation